Polyadenosine diphosphate-ribose polymerase inhibitors: advances, implications, and challenges in tumor radiotherapy sensitization - Zhang, Yi; Liang, Lijie; Li, Zheng; Huang, Ying; Jiang, Ming; Zou, Bingwen; Xu, Yong (Frontiers in Oncology, 2023)
Polyadenosine diphosphate-ribose polymerase (PARP) is a key modifying enzyme in cells, which participates in single-strand break repair and indirectly affects double-strand break repair. PARP inhibitors have shown great potential in oncotherapy by exploiting DNA damage repair pathways, and several small molecule PARP inhibitors have been approved by the U.S. Food and Drug Administration for treating various tumor types. PARP inhibitors not only have significant antitumor effects but also have some synergistic effects when combined with radiotherapy; therefore they have potential as radiation sensitizers. Here, we reviewed the advances and implications of PARP inhibitors in tumor radiotherapy sensitization. First, we summarized the multiple functions of PARP and the mechanisms by which its inhibitors exert antitumor effects. Next, we discuss the immunomodulatory effects of PARP and its inhibitors in tumors. Then, we described the theoretical basis of using PARP inhibitors in combination with radiotherapy and outlined their importance in oncological radiotherapy. Finally, we reviewed the current challenges in this field and elaborated on the future applications of PARP inhibitors as radiation sensitizers. A comprehensive understanding of the mechanism, optimal dosing, long-term safety, and identification of responsive biomarkers remain key challenges to integrating PARP inhibition into the radiotherapy management of cancer patients. Therefore, extensive research in these areas would facilitate the development of precision radiotherapy using PARP inhibitors to improve patient outcomes.